Investigating the prevalence of primary open-angle glaucoma among patients with systemic hypertension: A cross-sectional study - Gudla Vasantha; Mounica Kakuturu; Bandari Teja Sri (Asian Journal of Medical Sciences, 2024)
Background: Primary open-angle glaucoma (POAG) is a significant cause of irreversible blindness worldwide. Aims and Objectives: This study aimed to investigate the prevalence of POAG among hypertensive patients. Materials and Methods: A comprehensive analysis was conducted on 200 hypertensive patients, categorizing them by gender, age groups, and blood pressure ranges. POAG was diagnosed using standardized criteria, and mean intraocular pressure (IOP) values were compared between POAG patients and normal individuals. The study also assessed the change in IOP across various ranges of systolic and diastolic blood pressure (SBP and DBP). Results: Among the hypertensive population, 5% of males and 3% of females were diagnosed with POAG, indicating a slightly higher prevalence in males. POAG incidence was notably higher in the 60–69 years of age group, suggesting a potential correlation with older age. Analysis of mean IOP values demonstrated significantly higher readings in both eyes of POAG patients compared to normal individuals, aligning with the hallmark of glaucoma. The distribution of hypertensive patients across different SBP and DBP ranges revealed that higher SBP levels (140–149 mmHg and ≥160 mmHg) were associated with more POAG cases. Similarly, elevated DBP levels (90–99 mmHg) showed the highest number of POAG cases. Conclusion: Our study suggests a slightly higher prevalence of POAG in male hypertensive patients and highlights older age as a potential risk factor. Elevated IOP, a characteristic feature of glaucoma, was confirmed in POAG patients. In addition, our findings indicate a potential association between higher SBP and DBP levels and an increased likelihood of POAG, emphasizing the importance of blood pressure management in glaucoma care.